Concomitant Fundoplication With Gastrostomy: A Two-State Comparison Showing Continued Use of Reflux Medications. Issue 6 (December 2016) - Fox, David; Campagna, Elizabeth J.; Finnell, S. Maria E.; Partrick, David A.; Kempe, Allison
ABSTRACT: Objectives: We sought to determine whether practice differences for fundoplication exist between 2 geographically distinct states, and to determine the reflux medication use pattern associated with concomitant fundoplication. Methods: A retrospective observational cohort study of children in Colorado (CO) and North Carolina (NC) insured by Medicaid from 2006 to 2008. Children who received a surgical gastrostomy during the study period were included, and our primary outcome measure was the performance of a concomitant gastric fundoplication. Thirty-day prescription fills for reflux medications were examined before and after gastrostomy procedure. Results: We examined 969 surgical gastrostomy admission in both states over the 3-year study period (CO, n = 341 and NC, n = 628). Patients in each state had similar age (median age, 6 months, P = 0.97). Use of pH probe (CO: 15%, NC: 11%) and diagnosis of reflux (CO: 84%, NC: 72%) differed in each state. Concomitant fundoplication was performed in 60% of patients in CO and 43% in NC ( P < 0.01). Age less than 6 months was associated with an increased adjusted odds of fundoplication in CO (OR 9.77, CI, 3.91, 24.43), but less so in NC (OR 2.73, CI, 1.48, 5.04). Among patients undergoing gastrostomy, the proportion of patients on reflux medication 4 to 6 months post-discharge did not differ between those receiving fundoplication and those that did not in either state. Conclusions: Rates of concomitant fundoplication varied in the 2 states despite patients having similar demographic and clinical characteristics. Antireflux surgery was not associated with a reduction in reflux medications in either state. Abstract : Supplemental Digital Content is available in the text